24. Live another day [videorecording (DVD)] - Sutherland, Kiefer, 1966-; Raver, Kim, 1969-; Donovan, Tate; Devane, William, 1939-
Exiled in London for four years, former counter terrorist unit agent Jack Bauer must spring into action to try to save U.S. President James Heller. In retribution for a drone strike he ordered, Heller sits in the crosshairs of the window of an al-Qaeda leader. Along the way, Jack faces his ex-love, Heller's daughter Audrey, who's married to chief of staff Mark Boudreau. Teaming with CTU operative-turned-hackivitst Chloe O'Brian, Jack risks everything to try to protect the U.S., prevent a global terrorist attack, and outrun the CIA head - as the pulse-quickening tension unfolds in real time!